Thermal decomposition kinetics of synthesized poly(N-isopropylacrylamide) and Fe3O4 coated nanocomposite: Evaluation of calculated activation energy by RSM - Pekdemir, Ersin; Aydogmus, Ercan; Arslanoglu, Hasan (Taylor & Francis Inc, 2024)
In this study, poly(n-isopropylacrylamide) (PNIPA) has been synthesized by the free-radical polymerization method using azobisisobutyronitrile the initiator. Then, nanoparticle-PNIPA composite is prepared with magnetic iron oxide (Fe3O4) nanoparticles synthesized by co-precipitation. The thermal decomposition kinetics of synthesized PNIPA and nanocoated PNIPA have been investigated. It has been observed that nanocoated PNIPA has a more stable structure at high temperatures than synthesized PNIPA. In the newly improved model equations relate to thermal decomposition kinetics, a special solution has been made with the new approach. Moreover, the calculated activation energies of the samples have been evaluated with response surface methodology (RSM). The ratios required to synthesize nanocoated-PNIPA under the optimum conditions have been determined by RSM. The activation energy of the nanocomposite obtains when 0.3170 g PNIPA is coated with 0.048 g Fe3O4 nanoparticle is determined as 127.757 kJ/mol. In other words, nanocoating has been increased the thermal stability of the synthesized composite.
Keywords: iron oxide; nanocoating; poly(n-isopropylacrylamide); RSM; thermal decomposition